OFW fathers and their children residential status, perceived paternal involvement and relationship satisfaction - Calasin, Joellie Marie Flor D.
This study analyzed the connection between a father?s residential status, child?s perceived paternal involvement, and father-child relationship satisfaction. A survey was conducted among 177 students aged 16 to 21 years old from three universities in Iloilo. The findings show that the residential status of the father does not affect the child?s perceived paternal involvement. Due to this, the relationship satisfaction of the two groups of children was almost the same with one another despite their father?s residential status. It was found that higher paternal involvement entails higher father-child relationship satisfaction. Regression analyses show that instrumental involvement does not predict satisfaction. For children with resident fathers, mentoring/advising involvement predict a better father-child relationship satisfaction. For children of OFW fathers, expressive and mentoring/advising involvements predict satisfaction.